ANTI-RACISM SEEN IN STEVEN SPIELBERG’S AMISTAD - DEWI, KARTIKA SARI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: racism, anti-racism, equality American is known as one of the countries which deals with racial issues. However, as time goes by, anti-racism begins to emerge. Anti-racism intends topromote an egalitarian society not to face discrimination due to their race.Amistad is a movie which shows that there are some characters that still havecompassion to each other without differentiating race or skin color. In this study, the writer analyzes the action and the statement to prove theanti racism shown by the characters in Amistad. The result of the study discoversthat anti-racism is manifested in some characters in this movie. They areTheodore Joadson, Lewis Tappan, Roger Sherman Baldwin, John Quincy Adam,Cinque, the Army, John Forsyth, Free Slaves. These characters are brave enoughto express their actions and thoughts to struggle against racism which isconsidered bad. They think that all people have the same right and deserve to get equal treatment in every aspect of life without any discrimination.It is suggested for the next researchers to conduct a study on the same filmwith other approaches, for example, psychological approach. This perspective can be used to identify the psychological condition of the characters in facing thechallenges in White majority society.